Impact behaviour and fractography of 6061 alloy with Trace addition of Sn - Monoj Baruah; Anil Borah (Fracture and Structural Integrity)
The impact behaviour of 6061 alloy with trace amount of 0, 0.04, and 0.08 wt.% Sn was studied in the as-cast (AC), as-roll (AR) and peak-age roll (PAR) processing state. Additionally, the fracture mechanism was also studied in the AC and PAR state. The experimental investigation revealed that at all processing states, trace addition of Sn improves the impact strength of the 6061 alloy. Compared to the other processing states, the PAR condition contribute most to the impact strength. Fractography analyses showed that the fracture in the alloys occurred primarily by the crack propagation of Al(Fe, Mn)Si particles. The fractures in the AC alloys took place by mixed ductile and brittle mode by larger ductile dimples, cracks and cleavages, while in the PAR alloys was primarily by ductile mode by the smaller dimple fractures.